Application of High Speed Continuous Casting on Low Carbon Conventional Slab in SGJT. Issue 11 (12th March 2014) - Li, Linping; Wang, Xinhua; Deng, Xiaoxuan; Wang, Xiaolian; Qin, Yiming; Ji, Chenxi
<x xml:space="preserve">Abstract</x> Based on the achievement of high speed continuous casting in SGJT, fluid flow, heat transfer, and lubrication behavior were analyzed elaborately. The results indicated that well‐bottom SEN with the angle of −20° together with FC mold could reduce the level fluctuation effectively. When FC mold was applied at 1.9 m min−1, there was an increase of average heat flux about 0.06–0.1 MW m−2. During heat transfer analysis, the empirical equation of heat flux was proposed and solidification crater end was validated by pin shooting method. Furthermore, a kind of mold powder employed in high speed casting was described and a new criterion of the consumption rate for high speed casting was put forward.